Improved HIV markers and decreased emergencyroom usage and hospital admission with initiation of a pilot specialty pharmacy at a southeastern Ryan –White –funded clinic over a three year period. (4th October 2017) - Ly Nguyen, Minh; Condra, Alton; Corbin-Johnson, Della; Woodson, Kay; Patel, Manish; Colasanti, Jonathan; Armstrong, Wendy
Abstract: Background: Specialty pharmacy (SP) provides timely medication delivery to patients and seeks to improve patient adherence through monthly pharmacist medication therapy management (MTM). Patients living with HIV/AIDS have both high cost medications and complex disease states and thus will benefit from SP. We report on the outcome of HIV therapy after 3 years of a pilot SP ina southern inner city RW funded clinic. Methods: This is a single center retrospective chart review of patients at our clinic who were enrolled in the SP from 6/3/13–5/1/16 for at least 6 months. Baseline demographic characteristics and HIV markers (CD4, viral load) were collected. Outcomes of interest were: change in CD4 count, percent with viral suppression (VS), emergency room (ER) and hospital admission usage, as well as percent of scheduled providers' appointment kept. Each individual had the same follow up time before and after SP initiation. Bivariate analysis compared outcomes preSP and during SP using Chi-square or Fisher exact tests for categorical and Wilcoxon rank-sum test for continuous variables. Results: During the 3-year period, there were 212 individuals referred to SP, of which 170 participated in the program. There were 92(54%) men, 136(80%) black. The median age was 48.3 years (IQR: 28.5–56.3). The average duration of follow up pre and during SP was 22.1(IQR: 16.5–27) months. In terms of insurance, 69(40%) had Medicare, 22(13%) had Medicaid, 22(13%) had private insurance, 54(32%) received AIDS drug Assistance Program (ADAP), and 3(2%) had Ryan White. Patients resided an average distance from the clinic of 17.4(IQR: 8.8–25) miles. The respective outcomes before and during SP were: CD4: 350(IQR: 181–551) vs. 413(IQR: 263–611 cells/mL ( P < 0.0001), VS in 78 ± 30% vs. 91 ± 20% ( P < 0.0001). The proportion of patients with emergency room usage or hospital admissions was 68(40%) vs. 49(29%) ( P = 0.036). There was no difference in the rate of kept providers' appointment (66.6 %(IQR: 53.8–78.6%) vs. 63.8 %(50-77%) ( P = 0.19). There was no reported death during the follow –up period. Conclusion: This pilot SP program at the RW clinic showed statistically significant improvement of CD4 count and VS, as well as 40 % decrease in odds of using ER or hospital admission. Further studies are needed to determine whether SP is beneficial to people living with HIV/AIDS in other settings. Disclosures: M. Patel, ViiV: Scientific Advisor, Consulting fee